Comparison of arthroscopic to open tibiotalocalcaneal arthrodesis in high-risk patients. Issue 6 (December 2019) - Baumbach, Sebastian Felix; Massen, Felix Kurt; Hörterer, Severin; Braunstein, Mareen; Waizy, Hazibullah; Böcker, Wolfgang; Polzer, Hans
Highlights: This is the first case control study comparing open to arthroscopic tibiotalocalcaneal arthrodesis (TTCA). This manuscript presents the largest cohort of arthroscopic TTCA published up to now. Open TTCA resulted in 63% major complications, predominantly surgical side infection. Arthroscopic TTCA resulted in 33% major complications, solely non-unions. Arthroscopic TTCA drastically reduced wound related complications. Abstract: Background: Open tibiotalocalcaneal arthrodesis (TTCA) is associated to high complication rates, which led to the development of arthroscopic techniques. Aim was to compare complication rates of open to arthroscopic TTCA in high-risk patients. Methods: Single-center, retrospective case-control study. Patients were selected from the authors' TTCA database. Eligible were high-risk patients receiving arthroscopic-, or open TTCA retrospectively suitable for arthroscopic TTCA. Primary outcome were major complications. Results: Eight open and 15 arthroscopic TTCAs were included. Three open and 4 arthroscopic TTCAs presented preoperative plantar ulceration. Fusion rates were similar (75% vs. 67%; p = 0.679). Major complications occurred in 63% of open (80% surgical-site-infections (SSI)) and 33% of arthroscopic (100% non-unions) TTCA. Preoperative plantar ulceration did not affect major SSI in open TTCA (67% vs. 60%) but resulted in a significant increase of non-union rates for arthroscopic TTCA (75% vs. 18%; p = 0.039). In patients without plantar ulceration the union-rate was 80% for both, open and arthroscopic TTCA. Conclusion: Arthroscopic TTCA drastically reduced major SSI. Patients without preexisting ulceration had excellent union-rates for open and arthroscopic TTCA.